2015
DOI: 10.1182/blood-2014-05-536060
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations and clinical impact of pediatric inherited thrombophilia

Abstract: The etiology of pediatric venous thromboembolic disease (VTE) is multifactorial, and in most children, 1 or more clinical risk factors are present. In addition, inherited thrombophilic disorders contribute to the development of pediatric VTE. In this review, the role of inherited thrombophilic disorders in the development of pediatric VTE, as well as the benefits and limitations of thrombophilia testing, will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
1
26
1
3
Order By: Relevance
“…At least one risk factor is identified in the majority of patients (1921). This stands in contrast to adults where 30–50% of VTE events are idiopathic or spontaneous.…”
Section: Incidencementioning
confidence: 99%
“…At least one risk factor is identified in the majority of patients (1921). This stands in contrast to adults where 30–50% of VTE events are idiopathic or spontaneous.…”
Section: Incidencementioning
confidence: 99%
“…The neonatal hemostatic system can be tipped toward thrombosis by a variety of acquired risk factors, and greater than 95% of neonatal VTE is associated with at least one clinical risk factor (5, 9) (Table 1). The most common clinical risk factor is the presence of a CVC (5, 913).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The most common clinical risk factor is the presence of a CVC (5, 913). A prospective study of neonates who underwent CVC placement indicated a 13% incidence of CVC-associated VTE (14), while another evaluating only umbilical catheter revealed a higher incidence of 22% (15).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…oral contraceptives, asparaginase). [5][6][7][8][9] In addition, several hereditary risk factors for thromboembolism have been discussed. 7 May-Thurner syndrome (MTS), a compression of the common iliac vein by the crossing common iliac artery, is observed in up to 50% of adult patients with descending iliofemoral DVT and is associated with a recurrence rate of up to 73% for thrombosis.…”
mentioning
confidence: 99%